Вы находитесь на странице: 1из 4

CLASS XII MATHEMATICS NCERT SOLUTIONS

Integrals
Exercise 7.1
Answers
1.

2.

3.

4.

d
( cos 2 x ) = 2sin 2 x
dx

An anti-derivative of sin 2x is

d
( sin 3x ) = 3cos 3x
dx

An anti-derivative of cos3x is

d 2x
d
e = e 2 x ( 2 x ) = 2e 2 x
dx
dx

An anti-derivative of e 2 x is

1
cos 2 x.
2
1 d
( sin 3 x ) = cos 3x
3 dx

d 1

cos 2 x = sin 2 x
dx 2

d 1

sin 3 x = cos 3 x
dx 3

1
sin 3 x.
3

1 d 2x
e = e2 x
2 dx

d 1 2x 2x
e =e
dx 2

1 2x
e .
2

d
3
2 d
2
( ax + b ) = 3 ( ax + b ) ( ax + b ) = 3 ( ax + b ) a
dx
dx
1 d
d 1
3
2
3
2

( ax + b ) = ( ax + b )
( ax + b ) = ( ax + b )

3a dx
dx 3a

5.

1 d
( cos 2 x ) = sin 2 x
2 dx

An anti-derivative of ( ax + b ) is

d
( cos 2 x ) = 2sin 2 x
dx

1
3
( ax + b ) .
3a
1 d
d 1

( cos 2 x ) = sin 2 x
cos 2 x = sin 2 x ..(i)
2 dx
dx 2

Again

d 3x
e = 3e3 x
dx

d 1 3x 3x
e =e
dx 3

d 4 3 x
3x
e = 4e
dx 3

[Multiplying both sides by 4 ]

.(ii)

Adding eq. (i) and (ii), we get


d 1
d 4 3 x
3x

cos 2 x + e = sin 2 x + ( 4e )
dx 2
dx 3

6.

d 1
4 3x
3x
cos 2 x e = sin 2 x 4e
dx 2
3

An anti-derivative of sin 2 x 4e3 x is

( 4e
=4

3x

1
4
cos 2 x e3 x .
2
3

+ 1) dx = 4e3 x dx + 1 dx = 4 e3 x dx + x

e3 x
+ x+c
3

ax

e ax

e
dx
=
and 1 dx = x

Material downloaded from http://myCBSEguide.com and http://onlineteachers.co.in


Portal for CBSE Notes, Test Papers, Sample Papers, Tips and Tricks

7.

2 x2
1
2
=
x
1

dx
x x2 dx =
x 2

( ax
=a

9.

=2

x3
+ ex + c
3

x dx +

2
1
1
1

+
dx = x + 2 dx
+2 x
x
x

x2
1
+ log x 2 x + c
dx 2 dx =
x
2

x3 5 x 2 4
x3 + 5 x 2 4
dx
=
x 2 + x2 x 2 dx =
x2
= x dx + 5 dx 4 x 2 dx =

12.

dx 1 dx

+ e x ) dx = 2 x 2 dx + e x dx = 2 x 2 dx + e x dx

( x)

11.

where c1 is the constant of integration.

10. x
dx =
x

1) dx =

+ bx + c ) dx = ax 2 dx + bx dx + c dx = a x 2 dx + b x dx + c 1 dx

x3
x2
+ b + cx + c1
3
2

(2x

x n +1
n
x
dx

=
if n 1

n +1

x3
x+c
3
8.

(x

( x + 5 4 x ) dx
2

2
x dx + 5 1 dx 4 x dx =

x2
4
+ 5x + + c
2
x

1
1
x3 3x 4
1
3 1

x3 + 3x + 4
1 + 1 + 1 dx = x 2 + 3x 2 + 4 x 2 dx
dx
=

x2 x2
x
1
1
5

= x 2 + 3x 2 + 4 x 2 dx =

+1

+1

x 2 dx + 3 x 2 dx + 4 x 2 dx
7

+1

3
1
x2
x2
x2
x2
x2
x2
2 7
+3
+4
+c =
+ 3 + 4 + c = x 2 + 2 x 2 + 8x 2 + c
=
5
1
1
7
3
1
7
+1
+1
+1
2
2
2
2
2
2

x3 x2 + x 1
dx =
13.
x 1
=
14.

2
x dx + 1 dx =

(1 x )

x dx =

x 2 ( x 1) + ( x 1)

( x 1)

dx =

( x 1) ( x 2 + 1)
( x 1)

dx =

(x

+ 1) dx

x3
+ x+c
3
3
12

2
x

x
=
x x x dx
dx =

x 2 dx x 2 dx

Material downloaded from http://myCBSEguide.com and http://onlineteachers.co.in


Portal for CBSE Notes, Test Papers, Sample Papers, Tips and Tricks

+1

+1

x2
x2
x2 x2
2 3 2 5

+c =
+
=
= x2 x2 + c
1
3
3
5
3
5
+1
+1
2
2
2
2
15.

x ( 3 x 2 + 2 x + 3) dx =

5
2

1
3
1
52

2
2
2
2
x
3
x
+
2
x
+
3
dx
3
x
+
2
x
+
3
x
=
(
)
dx

3
2

1
2

= 3x dx + 2 x dx + 3x dx
5
+1
2

=3

3
+1
2

1
+1
2

x
x
x
+2
+3
+c
5
3
1
+1
+1
+1
2
2
2
7

x2
x2
x2
= 3 +2 +3 +c
7
5
3
2
2
2
3
6 72 4 52
2
= x + x + 2x + c
7
5

16.

( 2 x 3cos x + e ) dx = 2 x dx 3cos x dx + e
= 2 x dx 3 cos x dx + e dx
x

dx

x2
= 2 3sin x + e x + c
2
2
= x 3sin x + e x + c
1

17.

1
2

3
2

x
x
x3
10 32
= 2 + 3cos x + 5 + c = 2 + 3cos x + x + c
3
3
3
3
2
3

18.

sec x ( sec x + tan x ) dx = ( sec


= sec x dx + sec x tan x dx

x + sec x tan x ) dx

= tan x + sec x + c

sec 2 x
dx =
19.
cos ec 2 x
=

+1

x3
x2
+c
2 x 2 3sin x + 5 x dx = 2 x 2 dx 3 sin x dx + 5 x dx = 2 3 ( cos x ) + 5
1
3
+1
2

1
cos 2 x
1 dx
sin 2 x

sin 2 x
2
cos2 x dx = tan x dx

Material downloaded from http://myCBSEguide.com and http://onlineteachers.co.in


Portal for CBSE Notes, Test Papers, Sample Papers, Tips and Tricks

( sec x 1) dx
= sec x dx 1 dx = tan x x + c
2

20.

2 3sin x
3sin x
2
dx =

dx
2
2
2
cos x
cos x cos x

( 2sec x 3 tan x sec x ) dx


= 2 sec x dx 3 sec x tan x dx
2

= 2 tan x 3sec x + c
21.

1
12

2
x
+
dx
x
+
x
=

dx

x
3

1
2

dx + x

1
2

+1

+1

x2
x2
dx =
+
+C
1
1
+1
+1
2
2

1
x2 x2
2 3
+
+ C = x 2 + 2x 2 + C
=
3
1
3
2
2
Therefore, option (C) is correct.

x4
x 3
1
3 3
4
4
3
4.

3
x
dx
x

3
+c
22. f ( x ) = 4 x 4 dx = 4 x dx 3 4 dx =
=

x
4
3
x

.(i)
f ( x ) = x4 + 3 + c
x
1
128 + 1

f ( 2 ) = 16 + + c
0=
+c
8
8
129
129

c+
=0
c=
8
8
129
Putting c =
in eq. (i),
8
1 129
f ( x ) = x4 + 3
x
8
Therefore, option (A) is correct.

Material downloaded from http://myCBSEguide.com and http://onlineteachers.co.in


Portal for CBSE Notes, Test Papers, Sample Papers, Tips and Tricks